Effects of a megafire on the arbuscular mycorrhizal fungal community and parameters in the Brazilian Cerrado ecosystem - Moura, Jadson B.; Souza, Rodrigo F.; Vieira-Júnior, Wagner G.; Lucas, Leidiane S.; Santos, Jose M.; Dutra e Silva, Sandro; Marín, César (Forest Systems, 2022)
Aim of the study: To evaluate the effects of a mega-fire on the arbuscular mycorrhizal fungi (AMF) community and parameters in soils under Cerrado vegetation.Study area: Chapada dos Veadeiros National Park, Goiás, Brazil. This site suffered the biggest fire in its history on October 10, 2017, with an affected area of 66,000 ha.Material and methods: We analyzed AMF spore density, roots’ mycorrhizal colonization rate, easily extractable glomalin (EEG), as well as the AMF genera present. These parameters were evaluated in burned and unburned areas of five common phytophysiognomies of the region.Main results: Fire presence immediately affected the mycorrhizal community parameters in Cerrado soils, which tended to increase afterwards. The presence of AMF genera did not differ between burned and unburned areas, with Acaulospora, Claroideglomus, Diversispora, Glomus, Funneliformis, Sclerocystis, and Gigaspora being present. The recovery of AMF community conditions in the Cerrado after fire events could also be observed in the mycorrhizal parameters evaluated, as the values of spore density, roots’ mycorrhizal colonization rate, and EEG were similar in the burned and unburned areas.Research highlights: AMF diversity, and especially their community parameters, show great recovery after fire events, since they are crucial in processes like nutrient cycling and soil aggregation.